Lassa fever: implications of T-cell immunity for vaccine development - ter Meulen, J (Journal of biotechnology, 1999)
Lassa fever is a re-emerging viral hemorrhagic fever, which causes significant human morbidity in endemic regions of West Africa. Attempts to vaccinate against this virus in animal models including non-human primates have revealed that eliciting a strong cellular immune response protects from clinical disease, but not infection, in the absence of measurable neutralizing antibodies. As there is renewed interest in developing a vaccine against Lassa fever for use in humans, several questions should be addressed in view of the scarce knowledge of the mechanisms of natural immunity against this disease. MHC-dependency of a vaccine relying mainly on the induction of T-cell immunity and its ability to cross-protect against different Lassa virus strains will be important issues. Furthermore, the question whether the vaccine can prevent human-to-human transmission of the virus should be discussed and the possibility that vaccination could predispose to immunopathology should be excluded. We are addressing some of the above mentioned problems concerning natural immunity through field studies in the Republic of Guinea, West Africa, and are presently studying the CD4 cell responses of Lassa antibody positive subjects on the basis of T-cell proliferation assays using recombinant Lassa virus proteins.